Effect of Place of Residence and Treatment on Survival Outcomes in Patients With Diffuse Large B-Cell Lymphoma in British Columbia. (25th February 2014) - Lee, Benny; Goktepe, Ozge; Hay, Kevin; Connors, Joseph M.; Sehn, Laurie H.; Savage, Kerry J.; Shenkier, Tamara; Klasa, Richard; Gerrie, Alina; Villa, Diego
Abstract : Background: We examined the relationship between location of residence at the time of diagnosis of diffuse large B-cell lymphoma (DLBCL) and health outcomes in a geographically large Canadian province with publicly funded, universally available medical care. Patients and Methods: The British Columbia Cancer Registry was used to identify all patients 18–80 years of age diagnosed with DLBCL between January 2003 and December 2008. Home and treatment center postal codes were used to determine urban versus rural status and driving distance to access treatment. Results: We identified 1, 357 patients. The median age was 64 years (range: 18–80 years), 59% were male, 50% were stage III/IV, 84% received chemotherapy with curative intent, and 32% received radiotherapy. There were 186 (14%) who resided in rural areas, 141 (10%) in small urban areas, 183 (14%) in medium urban areas, and 847 (62%) in large urban areas. Patient and treatment characteristics were similar regardless of location. Five-year overall survival (OS) was 62% for patients in rural areas, 44% in small urban areas, 53% in medium urban areas, and 60% in large urban areas ( p = .018). In multivariate analysis, there was no difference in OS between rural and large urban area patients (hazard ratio [HR]: 1.0; 95% confidence interval [CI]: 0.7–1.4), although patients in small urban areas (HR: 1.4; 95% CI: 1.0–2.0) and medium urban areas (HR: 1.4; 95% CI: 1.0–1.9) had worse OS than those in large urban areas. Conclusion: Place of residence at diagnosis is associated with survival of patients with DLBCL in British Columbia, Canada. Rural patients have similar survival to those in large urban areas, whereas patients living in small and medium urban areas experience worse outcomes. Abstract : The main objective of this analysis was to examine the relationship between location of residence and mortality in patients with diffuse large B-cell lymphoma diagnosed and treated in British Columbia, Canada. Findings show that rural patients have similar survival to those in large urban areas, whereas patients living in small and medium urban areas experience worse outcomes.